Tradition of Burning Barges in Rokan Hilir Regency: Arts and Culture Studies - Esi Gusrini, Esi; Agustina, Agustina (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
Every society inherits traditions from its predecessors, creating a cultural continuum that defines social identity. In Indonesia, one of the unique cultural traditions is the Barge Burning Ritual, known as